Investigating the strength of polystyrene as aggregate replacement to produce ligthweight concrete wall panel - Aziemah, Hashim (2016)
This study was conducted to determine the compressive strength of lightweight concrete (LWC) containing expended polystyrene (EPS) or most known as polystyrene beads which is designated for load bearing wall application. In order to produce the LWC, EPS beads were chosen as lightweight aggregate because it gives advantages in term of their characteristic such as low density, high strength, good thermal and sound insulation. Besides that, it was also suitable for structure that would be exposed to impact like shear wall. In this study, twelve (12) unreinforced concrete wall panel with dimension 100 x 600 x 600 mm were produced. The size of polystyrene beads were 3.0 mm in diameter. There are four (4) concrete mix proportion that were used in this study which is (1:3:0), (1:2.5:0.5), (1:2:1) and (1:1.5:1.5). All sample were tested at Heavy Structure Laboratory, University Malaysia Pahang. The lightweight concrete wall panel were tested by using Magness Frame machine in order to get the ultimate axial and deflection parameter. The concrete wall panel were setup under pinned- fixed end condition. Then ultimate axial load of wall panel were determine by using British Standard (BS98110-97). Based on the test conducted, the compressive strength of lightweight concrete cube for RATIO 2 is the highest which is 20.645 N/mm2 while the lowest is RATIO 3 with strength 16.545 N/mm2.While for ultimate axial load, the maximum ultimate axial load at 28 days is RATIO 1 which is 194.79 kN and the lowest is RATIO 3 with 136.25 kN. Hence, when compare between RATIO 1 with the CONTROL, the difference of strength of wall panel did not give significant difference. There only small margin of differences of both specimen. Meanwhile, for deflection the data recorded by Linear Variable Differential Transformer (LVDT) are inconsistent. This is because the concrete wall panel were experience the compression and tension during the test conducted.